A small-molecule inhibitor of hypoxia-inducible factor prolyl hydroxylase improves obesity, nephropathy and cardiomyopathy in obese ZSF1 rats. - Pierre E Signore (Public Library of Science (PLoS), 2021)
Prolyl hydroxylase (PH) enzymes control the degradation of hypoxia-inducible factor (HIF), a transcription factor known to regulate erythropoiesis, angiogenesis, glucose metabolism, cell proliferation, and apoptosis. HIF-PH inhibitors (HIF-PHIs) correct anemia in patients with renal disease and in animal models of anemia and kidney disease. However, the effects of HIF-PHIs on comorbidities associated with kidney disease remain largely unknown. We evaluated the effects of the HIF-PHI FG-2216 in obese ZSF1 (Ob-ZSF1) rats, an established model of kidney failure with metabolic syndrome. Following unilateral nephrectomy (Nx) at 8 weeks of age, rats were treated with 40 mg/kg FG-2216 or vehicle by oral gavage three times per week for up to 18 weeks. FG-2216 corrected blood hemoglobin levels and improved kidney function and histopathology in Nx-Ob-ZSF1 rats by increasing the glomerular filtration rate, decreasing proteinuria, and reducing peritubular fibrosis, tubular damage, glomerulosclerosis and mesangial expansion. FG-2216 increased renal glucose excretion and decreased body weight, fat pad weight, and serum cholesterol in Nx-Ob-ZSF1 rats. Additionally, FG-2216 corrected hypertension, improved diastolic and systolic heart function, and reduced cardiac hypertrophy and fibrosis. In conclusion, the HIF-PHI FG-2216 improved renal and cardiovascular outcomes, and reduced obesity in a rat model of kidney disease with metabolic syndrome. Thus, in addition to correcting anemia, HIF-PHIs may provide renal and cardiac protection to patients suffering from kidney disease with metabolic syndrome.